Endemic Severe Fever with Thrombocytopenia Syndrome, Vietnam - Xuan Chuong Tran; Yeojun Yun; Le Van An; So-Hee Kim; Nguyen T. Phuong Thao; Phan Kim C. Man; Jeong Rae Yoo; Sang Taek Heo; Nam-Hyuk Cho; Keun Hwa Lee (Emerging Infectious Diseases, 2019)
Severe fever with thrombocytopenia syndrome (SFTS), a tickborne viral disease, has been identified in China, South Korea, and Japan since 2009. We found retrospective evidence of SFTS virus (SFTSV) infection in Vietnam, which suggests that SFTSV infections also occur in Vietnam, where the virus has not been known to be endemic.